Relationship between physical activity and health and quality of sleep of inactive people - Lukšaitė, Agilė; Matulevičiūtė, Eva; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2022)
The World Health Organisation has given recommendations about frequency, intensity, type of physical activity, which are necessary seeking to avoid chronical diseases. Recommendations are directed towards increasing a general physical activity in the least active human populations. Worldwide, as many as 23 % of adults are not sufficiently physically active. The lifestyle of 40–60 % of people living in the European Union is largely sedentary, therefore it is necessary to encourage people to change their sedentary lifestyle to a healthier and more active one. Aim. To analyse factors of physical activity which have an effect on health and quality of life of inactive people. Methods. To review scientific literature related to human health, quality of sleep, physical activity and to provide insights. A search for sources of literature on the topic under consideration was carried out using the electronic academic research databases of the World Health Organisation, ClinicalKey, PubMed, Google Scholar. Articles in the English language published between 2012 and 2022, which were in line with the research subject, were used for the review. The search was carried out using the key words and world combinations with them (physical activity, health, insomnia, prevention). The total of 26 full text sources on the theme under consideration were included in a systematic review. Results. Physical activity has an effect on the quality of sleep and through certain physiological mechanisms decreases the risk of insomnia. Levels of physical activity are of importance to health strengthening. Too weak, passive physical activity reduces the quality of sleep and is related to the risk of insomnia. Conclusions. 1. A continuing stressful situation has a negative effect on the quality of people’s sleep. Physical activity, which does not comply with the WHO recommendations can have a negative impact on psychical, mental health and the quality of sleep. 2. Regular physical activity has a positive impact on mental health, activates neurobiological systems, encourages secretion of hypnogenic substances which improve the quality of people’s sleep.